Tinjauan Hukum Positif dan Hukum Islam terhadap Orang Yang Menyamar sebagai TNI Gadungan dengan Motif Penipuan - M. Khris Aditya Fajari; Erniwati; Purnomo, Bitoh (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2024)
With the advancement of technology, there are more and more frauds using technology, such as fraud using SMS, telephone and even internet fraud. There are many ways in which fraudsters can carry out their actions. The type of research used in this research uses library research. The results of this research, according to positive law, are explained in article 378 of the Criminal Code, imposing a sentence on the defendant with imprisonment for 3 (three) years and 6 (six) months. According to Islamic law, fraud is subject to Ta'zir punishment, namely in the form of legal bond and exile, legal differences positively subject to article 378 of the Criminal Code, namely a prison sentence of 3 years and 6 months, whereas in Islamic law, Jarimah ta'zir is imposed, namely the law of binding and exile. The same applies to providing sanctions to perpetrators who are proven guilty, namely perpetrators of people posing as fake TNI with fraudulent motives and the sanctions given are aimed at providing a deterrent effect for acts carried out by force as determined by written regulations.